Relationship between irritable bowel syndrome and plasma and tissue ghrelin levels - Şahin-Eryılmaz, Gülcan; Başak, Kayhan; Çakır-Madenci, Özlem; Koç, Hacer; Tüzün, Sabah; Dolapçıoğlu, Can; Ahıshalı, Emel; Dabak, Mustafa Reşat (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: This study aimed to evaluate the relationship between irritable bowel syndrome (IBS) and plasma and tissue ghrelin levels. Materials and Methods: Patients who had undergone gastroscopy procedure for any reason previously were enrolled in the study. Among these, patients with IBS symptoms were evaluated according to the Roma III criteria. The healthy control group comprised patients with no IBS symptom and had undergone gastroscopy procedure for another reason. The plasma ghrelin level and tissue ghrelin level obtained by immunohistochemical examination of biopsy specimens taken from the gastric antrum and corpus were evaluated in all participants. Results: The mean age of 90 participants was 43.64±12.64 years. The median value of the plasma ghrelin level was 3.29 (1.2-12.7) in the diarrhea group (IBS-D), 1.49 (0.82-7.08) in the constipation group (IBS-C), and 1.5 (0.2-3.7) in the control group. The plasma ghrelin levels between the groups were found to be significantly higher in IBS-D than in IBS-C and the control groups (p=0.001 and p=0.001, respectively). On comparing antral mucosal gland biopsy outcomes among the groups, staining intensity score was found to be significantly high in IBS-C as compared with the control group, whereas no significant difference was observed between IBS-D and the control groups (p=0.020 and p=0.429, respectively). Conclusion: The plasma ghrelin level in IBS-D and the staining intensity in the antral mucosal gland in IBS-C were found to be significantly higher. In addition, there was no difference between the groups in terms of ghrelin staining intensity in the gastric corpus. Cite this article as: Şahin-Eryılmaz G, Başak K, Çakır-Madenci Ö, et al. Relationship between irritable bowel syndrome and plasma and tissue ghrelin levels. Turk J Gastroenterol 2018; 29: 631-5.